Penentuan Umur Dump Truck dengan Metode Optimal Replacement Interval di CV. X - Yuli Setiawannie; Nita Marikena; Sindi Sania Putri (Universitas Harapan Medan, 2021)
Every asset in the operation of certain services, transportation or services will experience a change in each period of time. Replacement is made on an asset that is damaged, operating costs are too high, or a change in technology makes an equipment unusable. CV. X is a company engaged in providing services for transportation fleets, one of which is dump trucks. Today, companies are often faced with complex replacement problems and only apply the depreciation method to determine the life of their equipment. This study aims to propose determining the age of dump trucks with optimal replacement intervals and to find out the hourly usage costs incurred by the company at the optimal replacement age. This method uses the hourly cost as the basis for determining the optimal replacement life. The research data is in the form of secondary company data consisting of maintenance data such as vehicle purchase price data, fuel consumption, lubricant consumption, labor wages, annual operating hours, productivity, rental rate, interest rate value, and income tax rate. The parameters are in 1000 hour intervals. The optimal replacement life for dump trucks is in the interval of 30,000 hours – 40,000 hours or 12-16 years. The hourly usage cost at the optimal replacement life interval with the productivity approach is 159.74 and the hourly usage cost with the rental rate approach is 104.64.